2010
DOI: 10.1111/j.1746-1049.2010.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Human Capital and Micro and Small Business in Lao PDR

Abstract: This paper examines the determinants of performance in 1,776 micro and small enterprises that represent all industry sectors and geographical regions in Lao PDR. Although considerable resources are being directed toward promotion schemes in the country, empirical research on this subject is very limited. This study provides concrete insights into development strategies, particularly investment in basic education. The impact of business experience is small and insignificant. The differences between urban and ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
11
0
2
Order By: Relevance
“…The result implies that entrepreneur's education would contribute to increasing business turnover or employment. Overall, the contribution of education to firm performance 13 is consistent with the findings in previous studies for developing countries, such as Pakistan (Kurosaki and Khan, 2004), Lao (Onphanhdala and Suruga, 2010), and Vietnam (Santarelli and Tran, 2013;Vixathep, 2013). …”
Section: Entrepreneurial Human and Social Capitalsupporting
confidence: 80%
See 3 more Smart Citations
“…The result implies that entrepreneur's education would contribute to increasing business turnover or employment. Overall, the contribution of education to firm performance 13 is consistent with the findings in previous studies for developing countries, such as Pakistan (Kurosaki and Khan, 2004), Lao (Onphanhdala and Suruga, 2010), and Vietnam (Santarelli and Tran, 2013;Vixathep, 2013). …”
Section: Entrepreneurial Human and Social Capitalsupporting
confidence: 80%
“…This result could also imply that the regression analysis might not comprehensively capture the relationship between education and successful entrepreneurship in the case of SMEs in Laos, most probably due to the quality of data on business turnover. Absence of impact of education on entrepreneurial performance is not uncommon for developing economies, such as Bangladesh's ready-made-garment industry (Vixathep and Matsunaga, 2015), Vietnam's manufacturing industries (Vixathep, 2013) and Laos (Onphanhdala and Suruga, 2010). The seemingly contradicting sign of the coefficient for lower secondary, vocational and technical education on employment is attributable to the inclusion of initial labor (lnlabor0) and a large difference in the samples (Table 4).…”
Section: Entrepreneurial Human and Social Capitalmentioning
confidence: 61%
See 2 more Smart Citations
“…However, they lack the resource bases, technologies and raw materials required for success in competition. Many studies have found that human and social capital have an insignificant impact on competition in Lao PDR (Onphanhdala and Suruga, 2010; Daovisan and Chamaratana, 2020a, b; Daovisan and Shen, 2020). Sayvaya and Kyophilavong (2015) uncovered a positive association with financial capital, although it is statistically insignificant.…”
Section: Introductionmentioning
confidence: 99%